Praktik Akuntansi di Era Global: Dampak IFRS dan Konvergensi Standar terhadap Kompleksitas Pelaporan Keuangan - Tiara Syafiqoh (Journal of Organizational Performance and Analysis, 2025)
This study explores the effect of financial statement quality on investment efficiency in the context of globalization and the adoption of International Financial Reporting Standards (IFRS). Financial statement quality contributes 17.9% to investment efficiency, while other factors such as debt duration also play a role. Globalization drives the need for international accounting standards, with IFRS improving the transparency and comparability of multinational companies' financial statements. Despite the benefits, IFRS implementation in Indonesia faces challenges such as cultural differences and lack of understanding. The impact of globalization affects stakeholders who depend on financial statements for decision-making. Therefore, efforts in education and regulation are needed to create a more efficient and transparent reporting system.